Perencanaan Tata Letak Fasilitas Mesin Produksi Menggunakan Metode Activity Relationship Chart(Arc) Di CV. Yasri Cipta Mandiri - Rokhmani, Eka Wahyu; Desiyanto, Fanni; Harsadi, Indrato (UNISTEK, 2021)
CV. Yasri Cipta Mandiri is a CV that was established in 2018, previously this industry was a polymer filter trading industry which is currently starting to produce its own polymer filters, this company produces Polymer Filters. on CV. Yasri Cipta Mandiri found that the production process was lacking in terms of the layout of the production machine or the layout that was less efficient in the degree of proximity so that distance had an unfavorable impact on the production process at CV. Yasri Cipta Mandiri and the addition of 1 new stamping machine unit, therefore it is necessary to improve the layout of the production machine facilities. For planning the layout of production machine facilities using the Activity Relationship Chart method. The total material handling distance or the total distance from each machine is 38.8 meters before the research is carried out. After processing the data and placing the work stations according to the degree of proximity using the activity relationshipship chart method, two proposed layouts were produced where these two proposed layouts were able to minimize the distance between work stations, the proposed layout I obtained a total material handling distance of 22.25 meters and obtained a value of 22.25 meters. efficiency is 42.65%, the proposed layout II obtained a total meterial handling distance of 20.46 meters and obtained an efficiency value of 47.26%, so that the proposed layout II is recommended as the selected proposed layout.